Engaging a product-focused sales force in solution selling: interplay of individual- and organizational-level conditions - Salonen, Anna; Terho, Harri; Böhm, Eva; Virtanen, Ari; Rajala, Risto (Journal of the Academy of Marketing Science, 2021)
Abstract This study explains how manufacturers tackle the critical managerial challenge of transforming a product-focused sales force to undertake solution selling. Through an application of configurational theory, the authors explain how individual and organizational conditions combine to determine salespeople’s engagement in solution selling. Multilevel, multisource data from the sales organization of a global supplier of building solutions represent input from salespeople ( N = 184), solution champions ( N = 23), and sales managers ( N = 26). A fuzzy set qualitative comparative analysis reveals no single, optimal way to overcome transformation challenges. Rather, consistent with prior research, solution selling requires certain types of salespeople, because value-based selling is a necessary condition for successful engagement. Beyond this foundational condition, a heterogeneous sales force can be engaged, as long as the organization provides appropriate support that is tailored to individual salespersons’ needs. The findings affirm that this viable support can come from either sales managers or solution champions.